Identification of Ethanol Extract Butterfly Pea Flower (Clitoria ternatea) with LC-HRMS and Antioxidant Activity Testing - Setya, Ninik; Syamsudin; Deni Rahmat; Nenden Lilis (Faculty of Pharmacy Universitas Pancasila, 2025)
Butterfly Pea Flower (Clitoria ternatea) is a plant rich in bioactive compounds, such as flavonoids, anthocyanins, and phenolic compounds, which have the potential to provide health benefits. This study aims to identify active compounds in butterfly pea flower extract and evaluate their antioxidant activity. Compound identification was performed using LC-HRMS is an analytical technique that combines liquid chromatography (LC) with high-resolution mass spectrometry (HRMS), while antioxidant activity was tested using radical scavenging DPPH (2,2-diphenyl-1-picrylhydrazyl). Analytical results showed that butterfly pea flower contain major flavonoid compounds, Butterfly Pea Flower contain compounds glycitein, quercetin, apigenin, kaemferol, laserpitin. The antioxidant activity test showed that Butterfly Pea Flower extract has a weak antioxidant capacity, which has the potential to counteract free radicals and reduce oxidative stress. These findings confirm that butterfly pea flower s have potential as a natural source of antioxidants that can be developed for pharmaceutical and functional food applications.